Some considerations relating to the statistics of Irish production and trade - Adams, W.G.S. (Statistical and Social Inquiry Society of Ireland, 1912)
Before proceeding to the considerations directly connected with the statistics of Irish Trade and Production, I should like to draw attention to a general question which bears on the matter under discussion. The growing importance of social and economic policy, the sense that all private business has a public side to it, and the need that public interests should be adequately safeguarded, present conditions which have favoured the development of State functions of inquiry and control. But these functions have been growing so gradually as to be hardly observed by men engrossed in affairs. It is only when a great step forward is made, such as the Census of Production Act, 1906 (6 Ed. VII., c. 49), that there is in the public mind a general heave of consciousness of the fact that the State has developed new eyes and ears and hands, and the ordinary suspicious mortal asks himself how it will affect taxation.
Read 11th June, 1909
Keywords: Foreign trade; Irish industry; 314.15